Rediscovering Pepper, Eggplant and Lettuce Landraces of the Valencian Community; An Ancient Resource with Vast Potential for the Future - Martínez-Ispizua, Eva (UPV (Universitat Politècnica de València), 2022)
Genetic erosion in crops, gained from prioritising production over quality, has led to biodiversity loss, which compromises global food security. By a historic selection process, farmers have been differentiating traditional crop varieties, which are a source of agricultural biodiversity that also favours the development of local economy, which makes their recovery, classification and cultivation key for food economy and the future. The conservation of traditional varieties requires knowledge of them, obtained from a detailed description of their phenotypical, agronomic and nutritional quality characteristics as added value. The Valencian Community (east Spain) has extensive horticultural heritage that is made up of a high diversity of traditional vegetable varieties. These are the result of adapting to the varied agroclimate conditions of the Valencian geography: on the one hand, the selection applied by farmers to each locality; on the other hand, these varieties are very valuable as ethnobotanical heritage and should be preserved. Moreover, the cultivation and consumption of traditional varieties are currently growing because they are particularly appealing to consumersfortheir diversity and high nutraceutical quality.